Sleep Quality, Insomnia, and Perceived Stress among Colombian Healthcare Workers during the COVID-19 Pandemic - Waich, Alan; Barahona-Correa, Julián Esteban; Figueredo, Maria del Carmen; Rondón-Sepúlveda, Martín Alonso; Ruiz, Alvaro J.; Castellanos, Julio Cesar; Hidalgo-Martínez, Patricia (Sleep Science, 2023)
Objective The COVID-19 pandemic has imposed a great burden on healthcare workers worldwide. The aim of the present study was to assess sleep quality, insomnia, and perceived stress in healthcare workers of a high complexity hospital located in Bogota, Colombia.Methods Cross-sectional study in which 1,155 healthcare workers at the Hospital Universitario San Ignacio in Bogotá, Colombia were included, between September and October 2020. Using an online-based survey, self-reported variables were assessed including demographics, Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), and 10 item Perceived Stress Scale (PSS-10). Associations between these variables were evaluated.Results Fifty percent of the respondents were between 31 and 45 years old, and 76 percent were women. Most of the surveyed were the nursing staff. Poor sleep quality, insomnia, and high perceived stress was found in 74.9, 12.4, and 13.2%, respectively. Poor sleep quality was predominantly found in females, in the 31 to 45 years old group and in married personnel. Also, poor sleep quality was found in relation to a moderate to high perceived risk of COVID-19 infection by the family of the workers surveyed.Discussion Poor sleep quality, moderate rates of insomnia, and perceived stress were found among healthcare workers committed to COVID-19 infected patients in Colombia. The identification of workers at greater risk and the implementation of targeted interventions are called upon as the results.
Keywords: healthcare workers; sleep quality; insomnia; stress; COVID-19; Latin America